2009
DOI: 10.1007/s10236-009-0247-9
|View full text |Cite
|
Sign up to set email alerts
|

On the response of a turbulent coastal buoyant current to wind events: the case of the Western Adriatic Current

Abstract: This numerical study focuses on the response of the Western Adriatic Current to wind forcing. The turbulent buoyant surface current is induced by the Po river outflow in the Adriatic Sea. Idealized and realistic wind conditions are considered by retaining the complex geomorphology of the middle Adriatic basin. In the absence of wind, the Adriatic Promontories force the current to separate from the coast and induce instabilities. Persistent 7-m s −1 downwelling favorable northwesterly winds thicken and narrow t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…Carlson et al (2016) showed how synoptic wind events can alter surface Lagrangian pathways in the Adriatic and, as such, COSMO winds at 10 m height are use to qualitatively examine the role of winds in the transport of floating AMD, following Carlson et al (2016). Basin-averaged wind is used as previous studies found high correlations in both magnitude and direction of surface winds over the Adriatic (Magaldi et al, 2010;Carlson et al, 2016).…”
Section: Regional Ocean Modelmentioning
confidence: 99%
“…Carlson et al (2016) showed how synoptic wind events can alter surface Lagrangian pathways in the Adriatic and, as such, COSMO winds at 10 m height are use to qualitatively examine the role of winds in the transport of floating AMD, following Carlson et al (2016). Basin-averaged wind is used as previous studies found high correlations in both magnitude and direction of surface winds over the Adriatic (Magaldi et al, 2010;Carlson et al, 2016).…”
Section: Regional Ocean Modelmentioning
confidence: 99%
“…Whitney and Garvine (2005) derive and test a scaling for the relative importance of wind versus buoyancy for the Delaware Coastal Current and show that for realistic wind events the wind forcing can dominate the flow. Using realistic and idealized numerical models, Magaldi et al (2010) showed that downwelling-favorable winds over the West Adriatic Current (along the east coast of Italy) intensify and stabilize the current and also induce mixing that dilutes the freshwater plume.…”
mentioning
confidence: 99%
“…At water depths greater than 70 m, late-Holocene muddy deposits are draped on the pre-existing erosional morphology of the area (Cattaneo et al, 2003). Between the two areas of deposition, the flat area is barren of modern muddy late-Holocene sediment, suggesting that, in this region, the Adriatic Coastal Current accelerating around the Gargano Promontory does not allow permanent deposition of mud, as predicted by oceanographic models (Magaldi et al, 2010). The barren area is characterized by the presence of shell gravel, bioclastic sand, rhodoliths, live oyster aggregates, and by an area of outcropping cemented rocks with a high backscatter on sidescan sonar and a rugged topography suggestive of differentially cemented or differentially eroded stratified rocks.…”
Section: Morphology Of Drowned Karst Featuresmentioning
confidence: 92%